Evaluation on the implementation of respiratory protection measures in old age homes - Lee DT (Dove Medical Press, 2017)
Diana TF Lee,1 Doris Yu,1 Margaret Ip,2 Jennifer YM Tang3 1The Nethersole School of Nursing, The Chinese University of Hong Kong, 2Department of Microbiology, The Chinese University of Hong Kong, Prince of Wales Hospital, Sha Tin, 3Sau Po Centre on Ageing, The University of Hong Kong, Pok Fu Lam, Hong Kong Purpose: Old age homes (OAHs) represent a vulnerable community for influenza outbreaks. Effective implementation of respiratory protection measures has been identified as an effective prevention measure to reduce mortality and morbidity caused by such outbreaks. Yet, relatively little is known about this aspect in these homes. This study evaluated the implementation of respiratory protection measures among infection control officers (ICOs) and health care workers (HCWs) in these homes in Hong Kong.Patients and methods: A territory-wide, cross-sectional survey was conducted in 87 OAHs. A total of 87 ICOs and 1,763 HCWs (including nurses, health workers, care workers, allied HCWs and assistants) completed the questionnaires that evaluated the implementation at the organizational level and individual level, respectively. Generalized estimating equations with unstructured working correlation matrix were used to analyze the simultaneous influence of organizational and individual factors on the implementation.Results: At the organizational level, all homes had a policy on respiratory protection and implementation of such measures was generally adequate. Basic resources such as paper towels/hand dryers and equipment disinfectants, however, were rated as most inadequate by HCWs. Training opportunities were also identified as grossly inadequate. Only less than half of the ICOs and HCWs participated in training on infection control either at the initiation of employment or on a regular basis. Twenty-five percent of HCWs even indicated that they had never participated in any infection control training. At the individual level, hand hygiene, among other protection measures, was found to be less well implemented by HCWs. In terms of the association of various organizational and individual characteristics, private homes and health workers rated significantly higher scores in the implementation of various domains in respiratory protection.Conclusion: Addressing the unmet training needs and promoting hand hygiene practice are efforts suggested to further enhance the implementation of respiratory protection measures in OAHs. Keywords: influenza outbreaks, health care workers, long-term care, infection control